English for Biomedical Scientists - Ribes, Ramón; Iannarelli, Palma; Duarte, Rafael F. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Biomedical scientists are the most likely health care professionals to actually move to an English-speaking country to continue professional training and career-development. This book should help to apply for jobs, write résumés, face job interviews and settle into a new working environment in English. The practical approach of the units will boost the readers' self-confidence in their own English-capabilities. This book should help reducing the anticipated stress of having to learn important matters directly "on the job", and secure more efficient and productive communication from the start.